"A glorious future" for Africa: development, higher education and the making of African elites in the United States (1961–1971). (4th May 2021) - Tarradellas, Anton
ABSTRACT: At the time of African independence, the concept of higher education for development took hold in the programmes of the new African governments and in the aid projects of the former colonial powers, the United States, the USSR, and international organisations. All agreed on the need to place higher education at the service of Africa's development and, to that end, to train the elites capable of carrying out the continent's modernisation. It was for this purpose that the African Scholarship Program of American Universities (ASPAU) was created, which enabled nearly 1, 600 Africans to study in the United States between 1961 and 1971. The objective of this article is to show, through the example of ASPAU, that beyond the almost unanimous support for the developmentalist project at the time of decolonisation, its conceptualisation and implementation have actually been shaped by differing expectations and relationships of domination. Governments, university officials, philanthropic foundations, and African students were all acting according to particular agendas that they tried to impose through different strategies. The training of African elites thus proved to be a much more tortuous process than was theoretically expected, fashioned as much by ideological concepts as by political interests, personal strategies and transnational flows of people and knowledge. In this sense, the history of ASPAU also highlights the deeply experimental dimension of decolonisation.